IMPLEMENTATION OF GROUP WORK IN THE CLASSROOM - Usman Karim (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2015)
One of the techniques which is a breakthrough to traditional lock step language teaching is group work. The traditional lockstep language teaching focuses teaching language on the explicit explanation of grammatical aspects, asking students to read and translate  line by line, memorizing difficult words, repeating words, phrases and sentences, and memorizing dialogues. This way, students tend to be passive and have lack of language practice in the classroom.  In other words, language teaching focuses on presenting grammatical knowledge, not on the use of language.  The traditional teaching now has been replaced by the various innovative and effective language teaching  techniques since the emergence of communicative language teaching in 1970s. One of them is group work.  Group work is learning together in a small group of four or five to work with language. Through group work, students can have more chance to practice the use of language in the classroom. Many research findings  show that group work is superior to traditional language teaching  in terms of learning achievement. Some of the activities which can be implemented through group work in the classroom are to be presented in this paper. They are game, role play, project, information gap, jigsaw, think pair and share, debate, enquiry technique, prioritizing (Expedition to Gunoeng Leuser), and fishbowl technique.